(3fbhd eNJdaIs
(3ChdgG (B:s
(3eeG ofbd ef OjhGf GdUHGHI dGHf CHj MLdI aj PcQ GdoMSf hCbSGeg, heG bjd ajgeG ef JaUjd hELeGd s
(3BNQgG (B:s
(3aj Chd gPG GdOYGA haj ChSWg hBNQg HbdH hgeI hYRjeI HMjK JLO ef faSc geI hfcJaj HgPg GdofHPI GdSjQI GdeHGQcI s
(3Vef eLehY s
(3efgG eG gh ef OjhGf GdUHGHI dGHf CHj MLdI aj GdoMSf hCbSGeg heG bjd ajgeG hef cJGH GdCZGfj dCHj GdaQLs
(3hYf CHf GdLhRjs
(3hJGQjN GdeSYhOj hef cJGH eYjO GdfYe hZjQgs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B165 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdCOHs